2012
DOI: 10.1021/la302721n
|View full text |Cite
|
Sign up to set email alerts
|

Earliest Stage of the Tetrahedral Nanochannel Formation in Cubosome Particles from Unilamellar Nanovesicles

Abstract: Studies of nonequilibrium lipid polymorphism at the nanoscale contribute to the in-depth understanding of the structural pathways for formation of aqueous channels and emerging of channels-network ordering in liquid-crystalline (LC) nanovehicles. We present experimental structural evidence for the smallest tetrahedral-type lipid membrane aggregate, which involves completely formed nanochannels and occurs as an early intermediate state during the bilayer vesicle-to-cubosome particle transition. Nanovehicles are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 54 publications
2
69
0
Order By: Relevance
“…To date only a few PEGylated lipids have been published as effective stabilizers for cubosomes (Fig. 8) [38,88,[197][198][199][200]202,[204][205][206]208]. The lipid anchors of these PEGylated lipids are explored in greater detail below.…”
Section: Pegylated Lipidsmentioning
confidence: 99%
See 3 more Smart Citations
“…To date only a few PEGylated lipids have been published as effective stabilizers for cubosomes (Fig. 8) [38,88,[197][198][199][200]202,[204][205][206]208]. The lipid anchors of these PEGylated lipids are explored in greater detail below.…”
Section: Pegylated Lipidsmentioning
confidence: 99%
“…The use of PEGylated phospholipids as a steric stabilizer for cubic nanostructured particles was reported by Angelov et al [204], Johnsson and Edwards [200], Zeng et al [205], and Koynova et al [197,198]. Angelov et al reported cubic nanostructured particles from aqueous dispersions of GMO and cis-5,8,11,14,17-eicosapentaenoic acid (20:5, EPA) in water, with 1,2-dioleoylphosphatidylethanolamine-PEG (DOPE-PEG 2000 ) as the steric stabilizer [204].…”
Section: Phospholipids (Dope Dspe and Dmpe)mentioning
confidence: 99%
See 2 more Smart Citations
“…Resulting dispersions are analogous to classical oil-in-water (o/w) emulsions but the oil phase, in this case, is replaced by a lipid selfassembly ( Figure 1). Structural organization of lipid self-assemblies in the bulk (non-dispersed form) and emulsions (dispersed form) is usually determined using small angle X-ray scattering (SAXS) and transmission electron microscopy (TEM) techniques [23][24][25]. Depending on the type of internal selfassembly, the nanostructured emulsions are recognized as cubosomes for cubic nanostructures, hexosomes for hexagonal nanostructures and so on [15,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%